Students' Understanding of Local Wisdom and Environmental Issues in Short Stories - Afandi, Iswan; Kharisma, Giri Indra (Lingua Cultura, 2024)
The purpose of this study is to describe students' understanding, which includes themes, character education (figures) who care about the environment, environmental issues, local wisdom, and students' expectations after reading short stories. The theories used are ecocriticism theory, local wisdom, and literary reception. This study is a descriptive qualitative study. Data sources, namely: 1) a questionnaire containing students' opinions on short stories and 2) five short stories by Jemmy Piran. Research data, namely student opinions, contained in the questionnaire. Data collection was carried out through a questionnaire. The data collection stage began with reading the five short stories, and then, students answered the questions in the questionnaire. The results of the analysis of students' understanding, namely: 1) the theme of the sea amounted to 0.80% and the theme of Harin Botan 0.25%; 2) data on students' understanding of environmentally conscious character figures as much as 1.60%; 3) data on fish population damage 0.51% and marine pollution 0.29%; 4) local wisdom includes traditional rituals amounting to 0.74%, beliefs 0.27%, local knowledge 0.27%, and customary law 0.09%; and 5) data on student readers' expectations about environmental preservation and local culture amounting to 1.34%. This study shows that local wisdom, such as traditional rituals and customary laws, is not only a culture but also an effective strategy for preserving the environment. The implication is that this understanding can enrich students' literacy regarding the importance of maintaining traditional values ​​in facing modern environmental challenges.